THE ACTIVITY OF HEALTHCARE INSTITUTIONS IN FERGHANA PROVINCE AND THE LEVEL OF THEIR MEDICAL SERVICE PROVISION TO THE VILLAGE POPULATION - Abdurakhmon Abdumuminovich Abdukhalimov (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the construction of new rural medical centers and repair of existing ones in Ferghana region, socio-economic status of medical institutions, outpatient clinics and polyclinics, providing them with the necessary medical equipment and laboratory equipment, attracting qualified specialists and providing quality medical care to the population are presented in the article. things are covered.